Efektivitas Kelompok Sebaya dalam Perilaku Berhenti Merokok di SMA Swasta Kota Denpasar - Ika Setya Purwanti; Ni Luh Putu Devhy (HB PRESS, 2020)
The smoking trend in adolescents is now increasing. The abuse of cigarettes in adolescents that cause addiction and can use negatives, such as the use of alcohol, drugs and others. Providing health education with peer education is one that can be given to address adolescent problems. Based on this background, the researchers wanted to know the effectiveness of peers groups on smoking cessation in adolescent boys. Method: This type of research is a pre-experimental research method, with a pre-post study design. The sample in this study was 32 adolescents played 15-18 years. The research was conducted at private vocational shool in Denpasar City. Results: Analysis of the data in this study used a statistical test and the average results of cigarette consumption before and after being given health education by peers decreased with a value of p <0.001, and as many as 69.2% of respondents asked for their help to smoke while getting health information from friends the same age. Solution: We recommend that schools implement peer education to give up smoking in adolescents.